Design-of-Experiments Analysis of Li-Ion Cell Capacity Fading in High Temperature Automotive Conditions - Stocker, Richard; Mumtaz, Asim; Lophitis, Neophytos (My University, 2019)
This paper examines the evolution of performance degradation through capacity fade in Li-ion cells when subjected to 8 months of automotive drive cycles in high temperature conditions. This is done by combining a temperature controlled, highly transient cycling approach with a design-of-experiments matrix varying charge current magnitude and Depth-of-Discharge, two factors known to be influential in ageing rate. The subsequent results are then analyzed using design-of-experiments methodology and trend analysis, comparing the rates of capacity evolution at various points in cell lifetime. What was found is that the cell ageing evolved in 3 main phases dependent on the cycling time duration rather than Ah throughput. In early life, charge current was influential, while in later life depth-of-discharge proved significant. It was also clear, that the factors could not be treated in isolation, with higher order and interaction effects observed. This implies that modeling of cell ageing cannot be uniform across lifetime and must consider the different ageing phases of the cell. Electric Vehicles International Conference (EV), 3-4 October 2019, Buthapest, Romania
Keywords: battery cell; equivalent circuit; Lithium-ion; model; simulation